Estudo da estrutura de complexos de polieletrólitos sobre as propriedades de transporte de água e sais - Vale, Rayane da Silva (2015)
Polyelectrolytes complexes (PECs) are defined as materials formed by combining oppositely charged polyelectrolytes together via ionic interaction. PECs have some unique physical properties such as non-solubility in common organic solvents, high surface hydrophilicity, tunable surface charge, and stable structures. A new type of PEC based on chitosan (CS) and sulfonate poly(ethylene terephthalate) (SPET) were synthesized in two different media, buffer solution and salt solution acidified with acetic acid. Fourier transform infrared spectroscopy (FTIR), zeta potencial, X-ray diffraction, thermal gravity analysis and differential scanning calorimetry were used to characterize the chemical structure, particle charge, crystallinity and thermal stability. To assess how the internal structure of the PEC and the subsequent membrane formation can affect water and salts transport capacity of microporous polycarbonate membrane, PECs solutions were spread via casting in commercial membranes with pore size of 5 μm. These membranes were characterized by Scanning Electron Microscopy (SEM), Water Vapor Flux, Resistance to Ion Migration and Membrane Potential. FTIR results indicated the electrostatic interaction of polyelectrolyte to form the polyelectrolyte complex. From the results of zeta potential it was found that the surfaces of CS/SPET nanoparticles have positive charges of about 25 to 44 mV. TGA curves showed that the PECs were more stable than their polyelectrolytes. The deposition of the PEC on the membranes was confirmed by SEM images and the increase of water vapor flux of membranes indicated that the presence of the complex significantly alter the hydrophilic profile of the polycarbonate matrix. The microfiltration of Saccharomyces cerevisiae cells demonstrated that membranes modified with PECs retained more of these organisms than the commercial membrane without modification.